2014
DOI: 10.1111/jofi.12084
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Varying Fund Manager Skill

Abstract: We propose a new definition of skill as general cognitive ability to pick stocks or time the market. We find evidence for stock picking in booms and market timing in recessions. Moreover, the same fund managers that pick stocks well in expansions also time the market well in recessions. These fund managers significantly outperform other funds and passive benchmarks. Our results suggest a new measure of managerial ability that weighs a fund's market timing more in recessions and stock picking more in booms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
184
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 483 publications
(211 citation statements)
references
References 63 publications
(101 reference statements)
24
184
2
1
Order By: Relevance
“…Kacperczyk et al, (2014) found that both timing and selection skills are not only time varying but also period specific. Furthermore, Mansor et al, (2015) suggest that the evidence of timing skills of Islamic mutual fund managers reported in the existing literature disappears once the time-invariant normality assumption is addressed.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations
“…Kacperczyk et al, (2014) found that both timing and selection skills are not only time varying but also period specific. Furthermore, Mansor et al, (2015) suggest that the evidence of timing skills of Islamic mutual fund managers reported in the existing literature disappears once the time-invariant normality assumption is addressed.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The major focus remained on the determination of abnormal return through stock selection abilities by using a standard CAPM model or a four-factor CAPM model. Finance literature on the other hand, clearly indicates that outperformance can be attributed to stock selection and/or the market timing ability of portfolio managers (Fama, 1972;Kacperczyk et al, 2014). In the case of IEIs, both stock selection and market timing can be attributed to the Shari'ah screening applied for index construction.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…A manager's excess returns over the benchmark, before fees, for his Funds 1 and 2 at time t , are given by truerightRt[]R1tR2t=[]ψ1+ε1tψ2+ε2t,where ψis, funds' expected excess returns, are partly fund‐specific and partly manager‐specific, that is, a manager can generate excess returns, but not necessarily by the same amount in the two funds (ψ 1 generally does not equal ψ 2 ) . While we do not model the source of these excess returns, we believe that managers could possess stock‐picking and market‐timing ability (Berk and Green (), Mamaysky, Spiegel, and Zhang (), Kacperczyk, van Nieuwerburgh, and Veldkamp ()) and that part of the two funds' excess returns can be attributed to the manager. Throughout the paper, we define the unobserved ability to generate expected (gross) returns in excess of a passive benchmark in the two funds as manager skill.…”
Section: A Model Of Managers With Two Fundsmentioning
confidence: 99%